S33 The utility of feno in the differential diagnosis of chronic cough: the response to anti-inflammatory therapy with prednisolone and montelukast. (15th November 2017) - Sadeghi, M Haji; Wright, C; Hart, S; Crooks, M; Morice, A
Abstract : Objectives: In this study we explored the effectiveness of treatment with montelukast 10 mg as compared with prednisolone in chronic cough patients with an associated elevated FeNO (The fraction of exhaled nitric oxide in breath) – a marker of eosinophilic inflammation. Methods: 50 non-asthmatic patients with chronic cough were recruited sequentially from a specialist cough clinic. 30 patients with high FeNO (≥30 ppb) were randomised to either two weeks prednisolone 20 mg or two weeks montelukast 10 mg followed by montelukast 10 mg for the subsequent two weeks in both arms. A control group of 20 patients with low FeNO (≤20 ppb) were enrolled who received four weeks montelukast. 24 hours cough counting at baseline after 2 and 4 weeks treatment was the primary endpoint. Subjective measures of cough, the Leicester Cough Questionnaire (LCQ), and Hull Airways Reflux Questionnaire (HARQ) were also administered. Results: At baseline the average FeNO value in both high FeNO treatment groups was similar (around 60±30 ppb). At the end of the study there was a significant fall in FeNO of approximately 30% in both high FeNO treatment groups (p < 0.005). In the low FeNO group there was no significant change during the study (12±5 ppb). Therapy reduced the number of coughs in 24 hours by approximately 50% in both low and high FeNO groups (p<0.005). HARQ and LCQ scores also improved significantly (p<0.005) in all treatment groups. Conclusions: The hypothesis that FeNO could be used as a marker of eosinophilic inflammation in chronic cough was supported by our observation at baseline in the high FeNO group of eosinophilia in both blood and sputum. However, baseline FeNO did not predict overall treatment response. Perhaps the most surprising aspect of our study is the dramatic response in the low FeNO group to montelukast. The fact that montelukast appears to be equally effective in the low FeNO group suggest the either the current markers of eosinophilic lung disease are insufficiently sensitive to pick up low levels of leukotriene activation in the low FeNO group, or that montelukast has its antitussive activity by an alternative mechanism.